Early surfactant for respiratory distress syndrome in premature infants - Scopesi, F.; Prodi, A.; Natalizia, et al., A.R. (Acta Biomedica Atenei Parmensis, 2013)
Effecs of early surfactant administration to premature newborns have been widely investigated in several RCTs. Furthermore, recent studies and metanalysis have compared early with delayed administration as well as selective and prophylactic use of surfactant.These data from the literature are discussed in the present review together with the factors that may argue against the standardization of respiratory care at birth. A tailored approach based on the stratification of risk factors may be appropriate in the so heterogeneous population of premature newborns.